Identify Lead Plumbing Sources to Protect Public Health. Issue 3 (1st March 2018) - Lytle, Darren A.; Schock, Michael R.; Triantafyllidou, Simoni
Abstract : Various drinking water sampling approaches can be taken to assess the presence of lead in drinking water. Water utilities should consider using diagnostic sampling to help identify lead sources.